EXPERIENCE OF USING ARGON PLASMA COAGULATION IN VIDEO-ASSISTED THORACOSCOPIC PARASTERNAL LYMPHODENECTOMY IN BRESAT CANCER PATIENTS - К. I. Kulaev; А. V. Vazhenin; О. S. Tereshin; К. S. Zuikov; I. Yu. Surovtsev (Сибирский онкологический журнал, 2016)
The experience of performing video-assisted thoracoscopic parasternal lymphadenectomy with the use of argon plasma coagulation for breast cancer patients has been presented. The proposed technique is effective in reducing the time of surgery and preventing blood lost. It also provides reliable final hemostatic control.